Criminalidad organizada, lavado de activos y extinción de dominio en el Perú - Acevedo Vásquez, Daniela Patricia (2022)
The large-scale criminal phenomena that characterize our contemporary history are those related to the constitution of criminal organizations. Criminal organizations have set up a new crime, the so-called macrocriminality; it has effectively provided large criminal gangs and drug traffickers with effective tools to make greater profits, allowing them to escape possible investigations into the provenance of their income. The new forms of crimes constituted by criminal organizations significantly exceed geographical and temporal borders, which is why Peru seeks to confront and fight against this type of crime through new criminal figures.